Avrupa Birliği'ne uyum sürecinde Türkiye'de çocuk hakları ve çocuk suçluluğu - Konuk, Gülşah (My University, 2019)
Çocuk hakları çalışmaları, İkinci Dünya Savaşı’ndan sonra hız kazanmış ve baştaBirleşmiş Milletler Çocuk Hakları Sözleşmesi olmak üzere uluslararası anlaşmalarladesteklenmiştir. Avrupa Birliği de bugün çocuk haklarını desteklemekte ve politikalarındaçocuklara ilişkin düzenlemelere yer vermektedir. Türkiye hem Birleşmiş Milletler üyesi hemde Avrupa Birliğine aday ülke olarak çocuk haklarına ilişkin düzenlemeleri takip etmektedir.Türkiye'de birçok konuda olduğu gibi çocuk haklarında da Avrupalılaşma düşüncesi etkindir.Avrupalılaşmaya ilişkin çalışmaların büyük ölçüde AB’ye indirgendiği ve AB öncesindekitarihsel sürecin ihmal edildiği görülmektedir. Bu çalışmada öncelikle Avrupalılaşma ve ABleşmeayrımı yapılarak, çocukluğun, çocuk haklarının ve çocuk suçluluğunun tanımına yerverilmiş, AB’de çocuk hakları ve çocuk suçluluğu ile Türkiye'de çocuk haklarının gelişimi vesuça sürüklenen çocukların durumu, Avrupalılaşma ve AB-leşme çerçevesinde ele alınmıştır.

The studies of children's rights gained momentum after the Second World War andwas supported by international agreements, in particular the United Nations Convention onthe Rights of the Child. Today The European Union supports children's rights so and includesregulations on children in their policies. As a member of the United Nations and a candidatecountry to the European Union Turkey is following the regulations on children's rights.Children's rights in Turkey, is effective as of the Europeanization of thought as in many issuesof it. It is seen that studies on Europeanization have been greatly reduced to the EU and thehistorical process before the EU has been neglected. In this study, firstly distinction betweenEuropeanization and EU-ization and definition of childhood, children’s rights and juveniledelinquency has been studied. Mainly focused on children’s rights in juvenile delinquency inEU and developing of children’s rights and juvenile delinquency in Turkey within theframework of Europeanization and EU-ization.
Keywords: AB-leşme Children’s rights; Avrupa Birliği; Avrupalılaşma; Çocuk hakları; çocuk suçluluğu; EU-ization; European Union; Europeanization; juvenile delinquency; Politics, Practical; Politika, Uygulamalı